2020
DOI: 10.3390/biology10010017
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Evolution of Receptor-Like Kinases (RLKs) and Receptor like Proteins (RLPs) in Brassica juncea

Abstract: Brassica juncea, an allotetraploid species, is an important germplasm resource for canola improvement, due to its many beneficial agronomic traits, such as heat and drought tolerance and blackleg resistance. Receptor-like kinase (RLK) and receptor-like protein (RLP) genes are two types of resistance gene analogues (RGA) that play important roles in plant innate immunity, stress response and various development processes. In this study, genome wide analysis of RLKs and RLPs is performed in B. juncea. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 103 publications
5
25
0
Order By: Relevance
“…The fewer RGAs in the individual sub-genomes of the Brassica polyploids compared to their diploid genome progenitor that we found in this study is consistent with the other Brassica RGA studies [ 11 , 96 , 109 , 110 , 111 , 112 ]. Duplicated disease R genes or RGAs are favourably lost in the sub-genomes of polyploid Brassicas after a duplication event compared to their diploid genome progenitors [ 109 , 110 , 113 , 114 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fewer RGAs in the individual sub-genomes of the Brassica polyploids compared to their diploid genome progenitor that we found in this study is consistent with the other Brassica RGA studies [ 11 , 96 , 109 , 110 , 111 , 112 ]. Duplicated disease R genes or RGAs are favourably lost in the sub-genomes of polyploid Brassicas after a duplication event compared to their diploid genome progenitors [ 109 , 110 , 113 , 114 ].…”
Section: Discussionsupporting
confidence: 93%
“…To perform the homology search, the protein sequence of each of the cloned genes was aligned across the seven genomes using translated Basic Local Alignment Search Tool (tBLASTn) using CoGeBlast [ 93 ]. Following the criteria used by previous studies identifying homologous genes in plants, tBLASTn hits with an E value range outside E0 to E-45 [ 94 , 95 , 96 ] or which did not have >70% similarity [ 96 , 97 , 98 , 99 ] were removed from further analyses. Since the smallest reference gene used in the study, At_Rpw8.1 , has 148 aa [ 75 ], any tBLASTn hits with <148 aa, were also removed from further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Study of RGAs of 30 species of Brassicaceae showed that between 5 and 14 LysM-RLK genes are present in the different assembly versions of B. napus [ 4 ]. The study of RLK and RLP in Brassica juncea also showed that the number of LysM-RLK genes in this plant is low and in contrast, LRR-RLK genes have a high frequency [ 4 , 81 ].The observed difference in the number of LysM-RLK genes identified in this study may be due to differences in detection criteria and differences in B. napus assembly versions. RLKs has been identified in many plants such as Arabidopsis thaliana , Oryza sativa , Brachypodium distachyon , Citrus sinensis , Triticum aestivum , Gossypium hirsutum , Pyrus bretschneideri , Malus domestica, Solanum tuberosum and B .…”
Section: Discussionmentioning
confidence: 99%
“…RLKs has been identified in many plants such as Arabidopsis thaliana , Oryza sativa , Brachypodium distachyon , Citrus sinensis , Triticum aestivum , Gossypium hirsutum , Pyrus bretschneideri , Malus domestica, Solanum tuberosum and B . juncea that containing 14, 20, 11, 9, 117, 60, 18, 21, 10 and 11 RLKs genes, respectively [ 16 , 17 , 39 , 40 , 43 , 78 , 81 , 82 ]. Due to the variability of the number of genes in different plant species, it can be concluded that the expansion of the LysM-RLK gene family is species-specific resulted from gene duplication events [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-seq has been widely applied to research including the analysis of gene expression and prediction of gene function since next-generation sequencing has been easily available to use. Several studies have reported the genome-wide identification of RLP genes in Arabidopsis, rice, tomato, Brassica, and legumes [ 24 , 29 , 30 , 31 , 32 , 33 ]. However, no previous study has reported the genome-wide transcriptional profiles in organ-specific of RLPs in pepper.…”
Section: Discussionmentioning
confidence: 99%